Energetic analysis on MR-X process for liquefaction of natural gas using open source software - Muhammad Nur Hafiz Shaidan (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Due to the increasing demand for natural gas in the world today, transportation of natural gas from different part of the world has become a necessity. Liquefying the natural gas provides a safer and cheaper alternative for transportation and also increases its storage capabilities. The liqefaction process reqires the natural gas to be cooled using various methods of cryogenic processes and also be depressurized to atmospheric conditions for easier and safer storage.